Multiple forms of discrimination and internalized stigma compromise retention in HIV care among adolescents: findings from a South African cohort - Pantelic, M; Casale, M; Cluver, L; Toska, E; Moshabela,M (Wiley, 2020)
INTRODUCTION: Efficacious antiretroviral treatment (ART) enables people to live long and healthy lives with HIV but young people are dying from AIDS-related causes more than ever before. Qualitative evidence suggest that various forms of HIV-related discrimination and resulting shame act as profound barriers to young people's engagement with HIV services. However, the impact of these risks on adolescent retention in HIV care has not been quantified. This study has two aims: (1) to examine whether and how different types of discrimination compromise retention in care among adolescents living with HIV in South Africa; and (2) to test whether internalized stigma mediates these relationships. METHODS: Between 2014 and 2017, adolescents living with HIV (aged 10 to 19) from 53 health facilities in the Eastern Cape, South Africa, were interviewed at baseline (n = 1059) and 18-month follow-up (n = 979, 92.4%), with responses linked to medical records. Data were analysed through multiple regression and mediation models. RESULTS: About 37.9% of adolescents reported full retention in care over the 2-year period, which was associated with reduced odds of viral failure (OR: 0.371; 95% CI: .224, .614). At baseline, 6.9% of adolescents reported discrimination due to their HIV status; 14.9% reported discrimination due to HIV in their families and 19.1% reported discrimination in healthcare settings. Healthcare discrimination was associated with reduced retention in care both directly (effect: -0.120; CI: -0.190, -0.049) and indirectly through heightened internalized stigma (effect: 0.329; 95% CI: 0.129, 0.531). Discrimination due to family HIV was associated with reduced retention in care both directly (effect: -0.074, CI: -0.146, -0.002) and indirectly through heightened internalized stigma (effect: 0.816, CI: 0.494, 1.140). Discrimination due to adolescent HIV was associated with reduced retention in care only indirectly, through increased internalized stigma (effect: 0.408; CI: 0.102, 0.715). CONCLUSIONS: Less than half of adolescents reported 2-year retention in HIV care. Multiple forms of discrimination and the resultant internalized stigma contributed to this problem. More intervention research is urgently needed to design and test adolescent-centred interventions so that young people living with HIV can live long and healthy lives in the era of efficacious anti-retroviral treatment.